CARDIOVASCULAR SCREENING IN NCAA ATHLETES: FINDINGS FROM A MULTICENTER ECG-INCLUSIVE PROGRAM. Issue 7 (11th March 2014) - Asif, I; Hadley, D; Harmon, K; Owens, D; Prutkin, J; Salerno, J; Drezner, J
Abstract : Background: The optimal pre-participation screening strategy in competitive athletes is debated. Objective: To evaluate the accuracy of cardiovascular screening in NCAA athletes using a standardized history, physical exam (PE), and electrocardiogram (ECG). Design: Prospective multi-center trial. Setting: Competitive US collegiate athletes from 17 schools. Participants: 3 284 athletes (56% male; 73% Caucasian; 15% African-American; mean age 19.8 years) from 17 sports were screened from July 2012 to October 2013. Assessment of risk factors: Screening included a standardized history and PE based on recommendations from the American Heart Association (AHA), and a resting 12-lead ECG interpreted using 2013 international consensus standards (Seattle Criteria). Main outcome measurements: Abnormalities detected by history, PE, and ECG. Results: 1 022 (31.1%) athletes had > 1 positive history response with SOB (11.6%%), syncope/near-syncope (11.0%), and exertional chest pain (6.5%) most common. PE was abnormal in 72 (2.2%) athletes. Overall, 123 (3.7%) ECGs were classified as abnormal (67.5% male, 32.5% female). The rate of abnormal ECGs was higher in men compared to women (4.5% vs 2.6%), African-Americans compared to Caucasians (5.3% vs. 3.6%), and most common in basketball players. A total of 133 ECG abnormalities were detected, including Q waves 36.8%, T wave inversion 22.6%, left axis deviation 9.8%, ST depression 7.5%, ventricular pre-excitation 6.8%, PVCs 5.3%, left atrial enlargement 4.5%, right ventricular hypertrophy 3.0%, prolonged QRS 2.3%, and prolonged QTc 1.5%. Eleven (0.3%) potentially lethal cardiac disorders were discovered. All 11 had abnormal ECGs, and only 2 cases had abnormal history or PE. Conclusions: The current AHA strategy for pre-participation screening generates a high number of false-positive responses in college athletes. ECG screening using modern standards for interpretation provides a low and acceptable rate of abnormal findings and greatly increases the identification of serious cardiac disorders in US collegiate athletes.